The Role of Kantor Virtual Applications as an Innovation in Administrative Management in the Management and Library Section of the Organization Bureau of the Regional Secretariat of the Province of Bali. - Dewi, Ni Putu Sukma Yuniantari; Wijaya, Komang Adi Sastra (Socio-political Communication and Policy Review, 2025)
The development of information technology in Indonesia shows a significant upward trend. One of the innovations developed by the Bali Province Communication and Information Office is the Virtual Office Application which is a virtual workspace application for all ASN and non-ASN employees within the Bali Provincial Government. This study aims to comprehensively analyze the role of the Virtual Office Application in improving administrative efficiency in the Management and Library Section of the Bureau of Organization of the Regional Secretariat of Bali Province. This research uses qualitative research methods with a descriptive approach. The results of this study are the use of the Virtual Office application is very visible and felt by employees. The increased speed in handling documents and the lack of complaints from users are clear evidence of its efficiency. This virtual office application has succeeded in changing the way of working to be more modern, effective, and transparent, thus supporting employee performance optimally.